Correlation and discordance of tumour proliferation index and molecular imaging characteristics and their implications for treatment decisions and outcome pertaining to peptide receptor radionuclide therapy in patients with advanced neuroendocrine tumour. Issue 8 (August 2015) - Basu, Sandip; Ranade, Rohit; Thapa, Pradeep
<x xml:space="preserve">Abstract</x> This communication critically illustrates the molecular imaging features and correlates them with the histopathological characteristics (focussing primarily on Ki-67 or MiB1 index) of neuroendocrine tumours (NETs), their implications for important treatment decision-making, and their response to peptide receptor radionuclide therapy. Such multiparametric analysis of functional imaging (along with conventional size, site-specific and stage-specific morphological assessment and histopathology) is crucial for developing a personalized model for the treatment of advanced and metastatic NET and to fine-tune the multimodal therapies, including the combination regimens. Illustrations with case examples have been made with respect to (a) concordant and (b) discordant tumour proliferation index and functional imaging features, (c) the variable molecular imaging parameters at the intermediate MiB1 indices, including (d) outliers with respect to their MiB1 index, and (e) interlesional heterogeneity between primary and metastatic sites in the same individual as demonstrated by molecular imaging features and its possible implications for therapeutic strategy. In each case, the treatment outcome has been described that would aid in better understanding of the potential usefulness of functional imaging in managing patients with NETs on an individual basis.